Comparative Efficacy of the New Optical Biometer on Intraocular Lens Power Calculation (AL-Scan versus IOLMaster) - Ha, Ahnul (Korean J Ophthalmol, 2018)
PURPOSE: To evaluate the agreement in axial length (AL), keratometry, and anterior chamber depth measurements between AL-Scan and IOLMaster biometers and to compare the efficacy of the AL-Scan on intraocular lens (IOL) power calculations and refractive outcomes with those obtained by the IOLMaster. METHODS: Medical records of 48 eyes from 48 patients who underwent uneventful phacoemulsification and IOL insertion were retrospectively reviewed. One of the two types of monofocal aspheric IOLs were implanted (Tecnis ZCB00 [n = 34] or CT Asphina 509M [n = 14]). Two different partial coherence interferometers measured and compared AL, keratometry (2.4 mm), anterior chamber depth, and IOL power calculations with SRK/T, Hoffer Q, Holladay2, and Haigis formulas. The difference between expected and actual final refractive error was compared as refractive mean error (ME), refractive mean absolute error (MAE), and median absolute error (MedAE). RESULTS: AL measured by the AL-Scan was shorter than that measured by the IOLMaster (p = 0.029). The IOL power of Tecnis did not differ between the four formulas; however, the Asphina measurement calculated using Hoffer Q for the AL-Scan was lower (0.28 diopters, p = 0.015) than that calculated by the IOLMaster. There were no statistically significant differences between the calculations by MAE and MedAE for the four formulas in either IOL. In SRK/T, ME in Tecnis-inserted eyes measured by AL-Scan showed a tendency toward myopia (p = 0.032). CONCLUSIONS: Measurement by AL-Scan provides reliable biometry data and power calculations compared to the IOLMaster; however, refractive outcomes of Tecnis-inserted eyes by AL-Scan calculated using SRK/T can show a slight myopic tendency.